Impact of Sustainable school design on primary school children's environmental attitude and behavior - Izadpanahi, Parisa; Elkadi, Hisham (2013)
This paper argues whether primary school children‘s environmental attitude and behavior is correlated with the sustainable design of their schools. 481 students were selected randomly from 3claimed sustainable designed and 3 conventional primary schools in Victoria, Australia. Data was collected through interactive keypads in groups of 50 each time. Analysis revealed that children, who are educated in claimed sustainable designed schools, possess higher proenvironmental attitude and more frequently behave environmental friendly compared to those in the schools with conventional architectural design. The paper also shows different environmental attitude and behavior based on gender differences.